Diurnal changes of net photosynthetic rate and chlorophyll fluorescence parameters of Cymbidium hybrid nobuko under different light intensities - WU Gen-liang; SUN Yao; SHEN Guo-zheng; HE Yong; ZHU Zhu-jun (浙江大学学报. 农业与生命科学版, 2009)
Diurnal changes of net photosynthetic rate and chlorophyll fluorescence parameters in one-year old and two-year old Cymbidium hybrid nobuko plants were investigated under three light intensities (full light intensity,36% of full light intensity and 18% of full light intensity). The results show that diurnal changes of net photosynthetic rate of one-year old C. hybrid were displayed two-peak curve under three light intensities. Under 36% of full light intensity and 18% of full light intensity, diurnal changes of net photosynthetic rate of two-year old C. hybrid were showed single curve. The one-year old and two-year old C. hybrids had low net photosynthetic rate under three light intensities. The changes of chlorophyll fluorescence parameter indicated that both of them had highest photosystem activity under 36% of full light intensity. Photo-inhibition of C. hybrid appeared under light intensity of 850 μmol·m-2·s-1, but could be relieved when photosynthetically active radiation (PAR) declined. C. hybrid leaves maintained high levels of chlorophyll fluorescence parameter and showed better response to light under light intensity of 364-400 μmol·m-2·s-1.